2019
DOI: 10.31557/apjcp.2019.20.11.3521
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cyclooxygenase-2 and Indoleamine 2,3-Dioxygenase Expression in Breast Cancer Patients from Pakistan

Abstract: 1996). Chronic inflammation is well known to be linked with cancer progression (Howe, 2007). Recent emerging epidemiologic, preclinical, and clinical data suggest that COX-2 up-regulation is a fundamental step in carcinogenesis (Cao and Prescott, 2002) and tumor angiogenesis (Davies et al., 2003). Elevated COX-2 expression has been detected in human breast tumor tissues (Ristimaki et al., 2002). The age-associated increase in COX-2 activity has been noticed in animal models (Claycombe et al., 2002). Elevated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In cancer types such as breast and colorectal, IDO1 co-expressed with cyclooxygenase-2 (COX2) is a weak independent predictor for overall survival [ 64 ]. Also, in triple-negative breast cancer, the expression of IDO1 has an association with forkhead box P3 (FoxP3) positive cells [ 65 ].…”
Section: Ido Expresses In Various Cancer Typesmentioning
confidence: 99%
“…In cancer types such as breast and colorectal, IDO1 co-expressed with cyclooxygenase-2 (COX2) is a weak independent predictor for overall survival [ 64 ]. Also, in triple-negative breast cancer, the expression of IDO1 has an association with forkhead box P3 (FoxP3) positive cells [ 65 ].…”
Section: Ido Expresses In Various Cancer Typesmentioning
confidence: 99%
“…It plays a physiological and pathological role by inducing arachidonic acid to transform into prostaglandin. Multiple malignant tumors may be promoted by COX-2 over-expression, which is brought on by the activation of growth factors, inflammatory cytokines, endotoxins, or oncogenes [9]. After down-regulation of COX-2 expression, it can promote cell apoptosis, inhibit angiogenesis, enhance cellular immunity and act as an anti-tumor agent [10more evidence is needed for clinical application.…”
Section: Figure1 Chemical Structure Of Oridoninmentioning
confidence: 99%
“…The team also proposed that inhibiting both of these pathways might act as a novel therapeutic strategy in breast cancer treatment[ 34 ]. Another study published by Asghar et al [ 35 ] reported that high IDO expression was correlated with high cyclooxygenase-2 expression in breast cancer patients. It was suggested that the simultaneous targeting of cyclooxygenase-2 and IDO may have potential for treatment of breast cancer[ 35 ].…”
Section: Therapeutic and Prognostic Significance Of Idomentioning
confidence: 99%
“…Another study published by Asghar et al [ 35 ] reported that high IDO expression was correlated with high cyclooxygenase-2 expression in breast cancer patients. It was suggested that the simultaneous targeting of cyclooxygenase-2 and IDO may have potential for treatment of breast cancer[ 35 ]. Carvajal-Hausdorf et al [ 36 ] observed that the IDO protein was expressed in hormone receptor-positive breast cancer.…”
Section: Therapeutic and Prognostic Significance Of Idomentioning
confidence: 99%